Immunohistochemical analysis of human CD5 positive B cells: mantle cells and mantle cell lymphoma are not equivalent in terms of CD5 expression. Issue 5 (1st May 2000) - Su, W; Yeong, K F; Spencer, J
Abstract : CD5 is expressed by most T cells and a subset of B cells. Human CD5 positive B cells are present in fetal lymphoid tissue, their frequency decreasing with fetal age. In adult human tissues, CD5 positive B cells have been reported to be present in the germinal centre and mantle zone. Malignancies of CD5 positive B cells include mantle cell lymphoma and chronic lymphocytic leukemia. This report describes an immunohistochemical staining technique used to visualise the expression of CD5 by B cells in human fetal intestine, tonsil, and mantle cell lymphoma. B cells in fetal intestine, tonsillar epithelium, and mantle cell lymphoma all had a similar high intensity of CD5 expression. In contrast, CD5 B cells in the mantle and germinal centre expressed very small amounts of CD5, below the threshold of the technique. Therefore, mantle cells and mantle cell lymphoma are not equivalent in terms of CD5 expression.